First on the List: Effectiveness at Self-Regulation and Prioritizing Difficult Exercise Goal Pursuit - Delose, Julie E. (Self Identity, 2014)
Identifying and understanding the goal pursuit strategies that distinguish effective self-regulators from less effective self-regulators is important for elucidating how individuals achieve their goals. We suggest that the timing of plans for difficult goal pursuits is one differentiation. A pilot study shows that effective self-regulators tend to believe they are best suited to pursue difficult goals earlier in the day, and two studies provide evidence that effective and less effective self-regulators differ in the timing of their plans for difficult goal pursuits. Results indicate that when exercising is perceived as difficult goal pursuit, effective self-regulators prioritize that difficult goal pursuit by planning to exercise earlier in the day whereas less effective self-regulators plan exercise for later in the day.